Functionalized poly(vinyl alcohol) as a novel dispersant for cement slurries: Synthesis, characterization and evaluation. (5th August 2020) - Liu, Xiao; Guan, Jianan; Lai, Guanghong; Qian, Shanshan; Zhao, Ming; Wang, Ziming; Cui, Suping
Graphical abstract: Highlights: A novel comb-structural PMA-g-PVA was synthesized and used as a promising dispersant. Functionalization of PVA can greatly enhance its thermal stability and dispersibility. Good plasticizing and retention capacities were shown for wide potential applications. Established a guiding equation for regulating the side chain length of comb polymer. Innovative design on molecular topological transformation helped PVA performances. Abstract: A novel dispersant for cement slurries or other suspensions was synthesized by graft copolymerization between maleic anhydride (MA) and end-functionalized poly(vinyl alcohol) (PVA) to produce comb polymer, i.e. PMA-g-PVA. The chemical structure was characterized by 1 H Nuclear Magnetic Resonance ( 1 H NMR), Infrared Spectroscopy (IR), Gel Permeation Chromatography (GPC), alcoholysis degree and element analysis. This functionalization of PVA can significantly enhance its thermal stability and dispersibility. The evaluations of PMA-g-PVA and PVA in cement slurries were comparatively discussed in detail. The results showed that PMA-g-PVA performed well in dispersing and dispersing retention capacities, presenting more excellent fluidities of cement slurry ( 200 mm) with maintenance of >85% within 3 h, due to its strong ability of breaking large flocculated structures of cement particles to fine size and homogeneous dispersion. This new type of functionalized PVA may be introduced as a promising candidate for the rheology modifying superplasticizer in slurry or colloid materials.